A comparative study into the effects of pre and post catalyst exhaust gas recirculation on the onset of knock. (September 2021) - Parsons, Dominic; Orchard, Simon; Evans, Nick; Ozturk, Umud; Burke, Richard; Brace, Chris
Exhaust gas recirculation (EGR) is proven as a valuable technology for controlling knock whilst maintaining lambda one operation, and is also capable of providing efficiency gains at low load. Despite this few studies in the literature address the question of EGR composition effects, namely whether the EGR gas is sourced from before or after the catalyst, and this remains an area which is often overlooked whilst investigating EGR performance. This paper demonstrates a novel method combining experiment air-path emulation and in-depth data processes to compare the effect of EGR catalysis on the angle of knock onset in a 1L GDI engine. Since initial temperature and pressure have a significant impact on knocking behaviour, an artificial boosting rig replaced the turbomachinery. This enabled fine control over the engine boundary conditions to ensure parity between the catalysed and un-catalysed cases. To overcome the difficulty of comparing stochastic phenomena in an inherently variable dataset, a pairing method was combined with Shahlari and Ghandhi's angle of knock onset determination method to assess the effects of EGR composition on knock onset for EGR rates ranging from 9% to 18%. The air path emulation system stabilised the engine combustion to provide a suitably rich dataset for analysing knock using the pairing method. Catalysed EGR improved the mean knock onset angle by 0.55 CAD, but due to the inherent variability in cylinder pressure data this only equated to a 58.3% chance of a later knock onset angle for catalysed EGR in any given pair of comparative cycles.